Cardio-protection of ultrafine granular powder for Salvia miltiorrhiza Bunge against myocardial infarction. (10th August 2018) - Wang, Linlin; Li, Yuanmin; Deng, Wen; Dong, Zhihui; Li, Xue; Liu, Dan; Zhao, Lijie; Fu, Weiguo; Cho, Kenka; Niu, Huaying; Guo, Dean; Cheng, Jinle; et al.
Abstract: Ethnopharmacological relevance: Myocardial infarction (MI) is considered as the major inducer to the morbidity and mortality related to coronary occlusion. Salvia miltiorrhiza Bunge is widely applied in the clinic for the prevention and treatment of heart diseases. The preparation of traditional herb decoction (THD) is not only time consuming but also difficult to keep uniform for every time. New usage form of Salvia miltiorrhiza Bunge with characteristics of convenience, uniform and efficiency is needed. Aim of the study: The aims of present study were to investigate the cardio-protection of ultrafine granular powder (UGP) of Salvia miltiorrhiza Bunge ; and further compare the characteristics of UGP with THD. Materials and methods: MI was induced by ligation of the left anterior descending coronary artery near the main pulmonary artery. Cardio-protection of UGP or THD was evaluated based on two sets of experiments, one was acute myocardial infarction (AMI) through 7 days preventive administration, and the other one was chronic cardiac remodeling through 28 days therapeutic administration. Hemodynamic measurement was conducted to evaluate heart function and histopathological detection was used to evaluate heart structure. Results: No significant improvement of heart structure and function was detected for preventive administration of UGP or THD on AMI rats. While, more significant improvements on left ventricular systolic and diastolic function were detected with therapeutic treatment with 0.81 g/kg UGP than same dose of THD on rats against chronic cardiac remodeling. Both UGP and THD showed the protective effects on heart structure, especially against fibrosis with long-term therapeutic treatment. Conclusions: As a new usage form of Salvia miltiorrhiza Bunge, UGP showed significant cardio-protection against myocardial remodeling with therapeutic treatment. Comparing with THD, UGP also holds the advantages of uniform, convenience and efficiency. Graphical abstract: